Max Weber's Theory of the Modern State Origins, Structure and Significance - Anter, Andreas; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Andreas Anter reconstructs Max Weber's theory of the modern state, showing its significance to contemporary political science. He reveals the ambivalence of Weber's political thought: the oscillation between an étatiste position, mainly oriented to the reason of state, and an individualistic one, focussed on the freedom of individuals.
Keywords: Political science; Political theory; Political economy; Democracy; Public policy; Political philosophy; Political Science and International Relations; Political Theory; Political Philosophy; Political Economy; Public Policy; Democracy; Political Science